(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this manuscrit, we establish some results on the existence and uniqueness of fixed points by using b-multiplicative metric spaces(MMS) endowed with a binary relation. we also find result on the coincidence of points involving a pair of mappings. Finally some examples are presented to illustrate the suitability of our results.